2004
DOI: 10.1111/j.1740-8261.2004.04094.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Harmonic Ultrasound of Spontaneous Liver Nodules in 32 Dogs

Abstract: Thirty-two dogs with spontaneous hepatic nodules were given intravenous ultrasound contrast medium (Definity or Sonovue) and imaged with contrast harmonic software on a conventional ultrasound machine system. Digital video images were initially reviewed to describe the perfusion pattern of malignant nodules. The images were reviewed again to test this pattern against all individual nodules. Subjectively, there was improved conspicuity of malignant nodules after contrast enhancement compared with conventional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 34 publications
8
127
2
1
Order By: Relevance
“…In addition, Levovist was shown to have hepatic parenchymal echo enhancement for a duration of over 7 min, whereas Definity was demonstrated to have hardly hepatic parenchymal echo enhancement [8]. In the previous report that used Definity, the post vascular phase was not observed [10]. In our study using Levovist, the contrast pattern that showed a defect in the complete tumor and an enhancement of the surrounding hepatic tissues in the post vascular phase were demonstrated in 7 of the 8 dogs, and their contrast patterns were similar to those in humans.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, Levovist was shown to have hepatic parenchymal echo enhancement for a duration of over 7 min, whereas Definity was demonstrated to have hardly hepatic parenchymal echo enhancement [8]. In the previous report that used Definity, the post vascular phase was not observed [10]. In our study using Levovist, the contrast pattern that showed a defect in the complete tumor and an enhancement of the surrounding hepatic tissues in the post vascular phase were demonstrated in 7 of the 8 dogs, and their contrast patterns were similar to those in humans.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, there is only one veterinary study that is reported in literature that has demonstrated CHI findings in 1 dog with HCC and in 3 dogs with metastatic hepatic HSA [10]. In the previous report, Definity was used as the contrast medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Namely, during the peak of parenchymal enhancement all malignant focal lesions were hypoechogenic. This occurrence (O'Brien et al 2004) correlates with the malignancy with a very high sensitivity, specificity, positive predictive value, negative predictive and accuracy (100%, 94.1%, 93.8%, 100% and 96.9%, respectively). (n=1) 1…”
Section: Ceus Clinical Applicationsmentioning
confidence: 96%